Effects of maximal strength training on bone mineral density in people living with HIV and receiving anti-retroviral therapy: a pilot study - Enock M. Chisati; Demitri Constantinou; Fanuel Lampiao (BMC, 2020)
Abstract Background Anti-retroviral therapy (ART) is associated with low bone mineral density (BMD) among people living with HIV (PLWHIV). Although physical activity is recommended for improving bone health in patients with reduced BMD, data on effects of strength exercises on low BMD among PLWHIV is scarce. This study therefore aimed to determine the effects of a 12 weeks maximal strength training (MST) on BMD among PLWHIV in Blantyre, Malawi. Methods Twenty-six PLWHIV with reduced BMD were randomised into a training group (TG, n = 15) and control group (CG, n = 11). The TG underwent 12 weeks of MST consisting of 4 sets of 3 to 5 repetitions at 85-90% of one repetition maximum (1RM) 3 times per week. The CG was advised to maintain their usual lifestyle. Measurements of BMD using dual-energy X-ray absorptiometry, 1RM using a squat machine, heart rate using a heart rate monitor, weight, height and body mass index were obtained before and after the intervention in the TG and CG. Descriptive statistics and student's t - tests were used to analyse data. Results The study was conducted for 12 weeks. Data of 24 participants [14 (TG) and 10 (CG)] were analysed. At base line, there were no significant differences in age (p = 0.34), height (p = 0.91), weight (p = 0.43) and body mass index (p = 0.34) between participants in the TG and the CG. After the intervention, there were significant improvements in lumbar BMD (p < 0.001) and resting heart rate (p = 0.03) in the TG compared to the CG. There were significant improvements in muscle strength (1 RM) in both the TG (p < 0.001) and the CG (p = 0.01). Conclusions MST improves lumbar BMD and strength in PLWHIV receiving ART in Blantyre, Malawi. MST with a shorter exercise duration of 12 weeks seem to have the potential in treating reduced BMD in PLWHIV. Trial registration PACTR201712002889203 . Registered with the Pan African Clinical Trial Registry on 22nd December, 2017 at www. pactr.org